Fragmentation studies of tetrahydropyridocarbazole derivatives by EI, ESI-MS/MS and FAB. Issue 1 (2001) - Romeiro Romeiro, Gilberto A. Gilberto A.; Ferreira Ferreira, Vitor F. Vitor F.; Costa Costa, Marília dos S. Marília dos S.; Joaquim Joaquim, Alexandre M. Alexandre M.; Carneiro Carneiro, José Walkimarde M. José Walkimarde M.; Kammerer Kammerer, Bernd Bernd
Abstract : Four tetrahydropyridocarbazole derivatives were analysed by different mass spectrometry techniques: electrospray ionization, fast atom bombardment and by low and high resolution 70 eV electron ionization. Retro Diels Alder is the main fragmentation pathway, whereas other pathways leading to [M—1] +, [M—CH3 ] + and double charge ions also occur to considerable extents. Semi-empirical calculation provided some evidence on the nature of tropylium ions [M—1] + . Calculation of ΔHf 0 indicated that [M + —1] could be formed preferentially when a hydrogen atom is lost from the methyl substituent of the homoaromatic ring.